Selection and shell relationship in Isocheles-sawayai forest and Saint-laurent, 1967 (crustacea, anomura, diogenidae) - Pinheiro, MAA; Fransozo, A.; Negreirosfransozo, M. L. (Inst Tecnologia Parana, 1993)
A populational sample of Isocheles sawayai Forest & Saint Laurent, 1967 was analysed in order to detect the validity of the shell aperture size as a parameter in the gastropod shell selection. The gastropods genus occupied by this hermit crab were: Thais, Buccinanops, Olivancillaria, Polinices and Cymatium. The power function (y = a.x(b)) was the best equation to represent biologically the regression analyses carried out among the measured parameters.
Keywords: HERMIT-CRAB; POPULATIONAL BIOLOGY; SHELL SIZE